ChemInform Abstract: Advances in the Discovery of Novel Antimicrobials Targeting the Assembly of Bacterial Cell Division Protein FtsZ. Issue 23 (June 2015) - Li, Xin; Ma, Shutao
Abstract Review: 139 refs.